Efek ekstrak daun singkong (Manihot utilissima) terhadap ekspresi COX-2 pada monosit yang dipapar LPS E.coli (The effect of Manihot utilissima extracts on COX-2 expression of monocytes induced by LPS E. coli) - Zahara Meilawaty (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Periodontal disease is a common and widespread disease in the community. Gram negative bacteria have a role inperiodontitis. These bacteria secrete a variety of products such as endotoxin lipopolysaccharide (LPS), which causes the occurrenceof inflammation or infection. The body defense responses are neutrophils and mononuclear cells (monocytes and macrophages). Inresponse to defense mechanism, the body will be expressed enzyme cyclooxygenase (COX) which functions convert arachidonic acidto prostaglandins. Cassava leaf cells known to play a role in reducing inflammation, but the mechanism for inhibiting COX-2, is notknown. Purpose: The study was aimed to determine the effect of cassava leaf extract (Manihot utilissima) on expression of enzyme COX-2 in monocytes which were exposed by LPS E. coli. Methods: This study was in vitro experimental studies with the design of posttestonly control group design. The sample was the cassava leaves extract (Manihot utilissima) at concentration of 12.5 % and 25 %. Theexpression of COX-2 was determined by immunocytochemistry method. Isolated monocytes were incubated in cassava leaf extract, andthen exposed to LPS, after washing imunostaning procedure was performed using a monoclonal antibody (MAb) anti-human COX-2.The research data was the number of monocytes that express COX-2. Results: Expression of COX-2 in the group cassava leaf extractwas higher than the group that induced by LPS E. coli only. Conclusion: Cassava leaf extract did not inhibit the expression of COX-2in monocytes which were exposed by LPS E. coli.Latar belakang: Penyakit periodontal merupakan penyakit umum dan tersebar luas di masyarakat. Bakteri yang banyak berperanpada periodontitis adalah Gram negatif. Bakteri ini mengeluarkan berbagai produk antara lain endotoksin lipopolisakarida (LPS) yangmenyebabkan inflamasi atau infeksi. Respon pertahanan tubuh pertama adalah netrofil dan sel mononuklear (monosit dan makrofag).Pada respon pertahanan tubuh akan diekspresikan enzim siklooksigenase (COX) yang berfungsi mengubah asam arakidonat menjadiprostaglandin. Daun singkong diketahui berperan dalam menurunkan sel radang, tetapi mekanisme dalam menghambat COX-2, belumdiketahui. Tujuan: Penelitian ini bertujuan untuk meneliti ekstrak daun singkong terhadap ekspresi enzim COX-2 pada monosit yangdipapar LPS E. coli. Metode: Penelitian ini merupakan studi eksperimental in vitro dengan rancangan The posttest only control groupdesign. Sampel adalah ekstrak daun singkong (Manihot utilissima) dengan dosis 12,5% dan 25%. Ekspresi COX-2 diteliti denganmetode imunositokimia. Isolat monosit diinkubasi ekstrak daun singkong, kemudian dipapar LPS, setelah pencucian kemudian dilakukanprosedur imunostaning menggunakan antibodi monoklonal (Mab) anti human COX-2. Data penelitian adalah jumlah monosit yang mengekspresikan COX-2.Hasil: Ekspresi COX-2 pada kelompok ekstrak daun singkong lebih tinggi dibandingkan kelompok yang hanyadiinduksi LPS E.coli. Simpulan: Ekstrak daun singkong tidak menghambat ekspresi COX-2 pada monosit yang dipapar LPS E. coli.